2x+4-(x+3)=3x-2+(2x-5)*4 3y-(5y+6)-2=-(y-4)+2y-12 полный ход решения уравнений.

Серггій26072006 Серггій26072006    2   01.07.2019 04:30    0

Ответы
Lerka1217 Lerka1217  24.07.2020 15:24
Получится вот так :)
2x+4-(x+3)=3x-2+(2x-5)*4 3y-(5y+6)-2=-(y-4)+2y-12 полный ход решения уравнений.
ПОКАЗАТЬ ОТВЕТЫ
Sasci Sasci  24.07.2020 15:24
№1
2х+4-(х+3)=3х-2+(2х-5)·4
2х+4-х-3=3х-2+8х-20
2х-х-3х-8х=-2-20-4+3
-10х=-23
х=-23:(-10)
х=2,3
№2
3y-(5y+6)-2=-(y-4)+2y-12
3y-5y-6-2=-y+4+2y-12
3у-5у+у-2у=4-12+6+2
-3у=0
у=0:(-3)
у=0
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика